Fra-1 and c-Fos N-terminal deletion mutants impair breast tumor cell proliferation by blocking lipid synthesis activation - Racca, Ana Cristina (2019)
Tumor cells require high rates of lipid synthesis to support membrane biogenesis for their exacerbated growth. The only two proteins known that activate phospholipid synthesis are Fra-1 and c-Fos, two members of the AP-1 family of transcription factors. These proteins that are overexpressed in human breast malignant tumors increase the rate of phospholipid synthesis at the endoplasmic reticulum through a mechanism independent of their nuclear function. The aim of this study was to inhibit breast tumor cell proliferation by modulating c-Fos and Fra-1 and regulate membrane biogenesis by controlling lipid synthesis rates. The molecular mechanism by which Fra-1 and c-Fos activate phospholipid synthesis was examined. Both proteins physically associate with the rate limiting enzyme CDP-DAG synthase through their N-terminus domain and activate it through their basic domain; neither protein associates to or activates the enzyme phosphatidylinositol synthase as determined through in vitro enzymatic reactions and FRET experiments. The N-terminus domain of both proteins act as negative dominant peptides that physically associate with CDP-DAG synthase but do not activate it. Proliferation of MDA-MB231 and 4T1 cells was impaired in vitro after inducing them to proliferate in the presence of the negative dominant peptides derived from Fra-1 and c-Fos. When tumors generated in Balb/c mice with the breast tumor cell line 4T1 were treated with these negative dominant peptides, a significant reduction in tumor growth was observed. Consequently, these Fra-1 and c-Fos negative dominant peptides can be exploited as a new therapeutic strategy to impair breast tumor cell proliferation.